Change management practices: harmonizing ISO9001:2008 and CMMI in the context of a Malaysian IHL - Garoot Eissal, Israa; Mohammed Farhan, Mysa; Ahmad Dahlan, Abdul Rahman (Imperial Journal of Interdisciplinary Research (IJIR), 2016)
This paper discusses the different between ISO9001:2008 and CMMI model in the context of Malaysian IHL with the focus on new System projects implementation. Using the Business Model Canvas (BMC) and the Value Proposition Design(VPD) to highlight some areas in which the adoption of CMMI within an ISO certified university setting can be a value creator. By conducting a gap analysis with the aim of identifying the university’s standing within the CMMI to enable to reach level 5 of the CMMI.